Islamic-Content-TED Public Speaking as a Source Material for Improving Islamic Student’s Communication Skill: Public Speaking TED Konten Islami Sebagai Sumber Materi Peningkatan Kemampuan Komunikasi Mahasiswa Islam - Kusuma, Lyla Anggerwina (JEES (Journal of English Educators Society), 2017)
In applying communicative competence that became the utmost teaching method in teaching English program, the lecturers found the fact that the Islamic communication students are apparently reluctant to speak and communicate their ideas confidently. It happens because they thought that they do not know what they are going to say and how they are going to say their ideas. By knowing these problems the lecturers then tried to analyze the sequences of Islamic-content-TED and integrate those public speaking sequences from TED talks to STID Al-Hadid’s students to give an understanding and also to improve the confidence and quality in delivering public speaking speech for the sophomore students who are majoring Islamic Communication & Broadcasting. For further, in order to master this skill, students are also expected to find noble ideas to be shared in their personal public speaking. This action research study then found out that having sharing the sequences of TED talks, the student’s public speaking productions are more organized and powerful moreover; the fluency and also the student’s accuracy of the students could be controlled well.